Key challenges related to smart villages - Niewiadomska, Agata (Przegląd Prawa Rolnego, 2023)
The aim of the considerations was to identify the challenges related to smart villages arising in the Polish and European legal systems. The expansion of the smart villages concept has become more apparent the new Common Agricultural Policy which provides for the development of different legal mechanisms which, put together, will help to create a smart village. The legal, but also social and economic challenges related to this proposal have been indicated and supported by examples of the implementation of innovative villages in selected European countries, taking into account the influence of globalisation and Europeanisation on the very concept of intelligent villages. Further to that, potential threats from the adopted solutions, as well as their impact on the competitiveness of agriculture have been highlighted. It has also been shown that intelligent villages constitute one of the transmitters of innovation in agriculture and digital rural development.